ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ЖӘҲАНША»: ЖЫЙНАЛЫЎ, БАСЫП ШЫҒАРЫЛЫЎ ҲӘМ ИЗЕРТЛЕНИЎ ТАРИЙХЫНАН - Мамбетов, Ж. (FAN va JAMIYAT, 2019)
The article deals with the main idea, plot, composition and publication of the Karakalpak folk epos «Zhakhansha» (in interpretation of Kurbanbay –jirau). The author of the article did the typological analysis of the heroes’ images, motives of their wandering with the purpose of getting knowledge and handicraft, and he also showed the peculiarities of the author’s individual style in the creation of the epos.